Plasmatic renin-angiotensin system in normotensive and hypertensive patients hospitalized with COVID-19 - Silva, Mauro Gastón (2022)
Background: Besides its counterbalancing role of the renin-angiotensin system (RAS), angiotensin-converting enzyme (ACE) 2 is the receptor for the type 2 coronavirus that causes severe acute respiratory syndrome, the etiological agent of COVID-19. COVID-19 is associated with increased plasmatic ACE2 levels, although conflicting results have been reported regarding angiotensin (Ang) II and Ang-(1−7) levels. We investigated plasmatic ACE2 protein levels and enzymatic activity and Ang II and Ang-(1−7) levels in normotensive and hypertensive patients hospitalized with COVID-19 compared to healthy subjects. Methods: Ang II and Ang-(1−7), and ACE2 activity and protein levels were measured in 93 adults (58 % (n = 54) normotensive and 42 % (n = 39) hypertensive) hospitalized with COVID-19. Healthy, normotensive (n = 33) and hypertensive (n = 7) outpatient adults comprised the control group. Results: COVID-19 patients displayed higher ACE2 enzymatic activity and protein levels than healthy subjects. Within the COVID-19 group, ACE2 activity and protein levels were not different between normotensive and hypertensive-treated patients, not even between COVID-19 hypertensive patients under RAS blockade treatment and those treated with other antihypertensive medications. Ang II and Ang-(1−7) levels significantly decreased in COVID-19 patients. When COVID-19 patients under RAS blockade treatment were excluded from the analysis, ACE2 activity and protein levels remained higher and Ang II and Ang-(1−7) levels lower in COVID-19 patients compared to healthy people. Conclusions: Our results support the involvement of RAS in COVID-19, even when patients under RAS blockade treatment were excluded. The increased circulating ACE2 suggest higher ACE2 expression and shedding.